Studying Cell Metabolism and Cell Interactions Using Microfluidic Devices Coupled with Mass Spectrometry - Wei, Huibin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This thesis describes a new approach for cell analysis by the rapid developing microfluidic technology. The nominee has made great contributions to develop a new analysis platform which combined microfluidic devices with mass spectrometry to determine the trace compounds secreted by cells. Based on this analysis platform, she studied the specific cell secreting behaviors under controlled microenvironment, of which the secretion compounds were qualified and semi-quantified by mass spectrometry. A novel cell sorting device integrated homogenous porous PDMS membrane was invented to classify cells from real samples based on the size difference. The nominee further studied the signal transmission between different cells, and the signal chemicals were qualitative and quantitative monitored by the analysis platform. This indicates the potential significant application of the new cell analysis platform in medicine screening and early diagnosis.
Introduction -- Analysis of Herbicides on a Single C30 Bead via the Platform Combined Microfluidic Device with ESI-Q-TOF-MS -- Monitoring of Glutamate Release from Neuronal Cell Based on the Analysis Platform Combining the Microfluidic Devices with ESI-Q-TOF-MS -- Microfluidic Device with Integrated Porous Membrane for Cell Sorting and Separation -- Cell Co-culture and Signaling Analysis Based on Microfluidic Devices Coupling with ESI-Q-TOF-MS.
Keywords: Chemistry; Analytical chemistry; Mass spectrometry; Cell biology; Nanotechnology; Chemistry; Mass Spectrometry; Nanotechnology and Microengineering; Cell Biology; Analytical Chemistry; Electronic books